PCSK9 inhibition and atherosclerotic cardiovascular disease prevention: does reality match the hype?. Issue 21 (8th June 2017) - Hadjiphilippou, Savvas; Ray, Kausik K
Abstract : Within this review we look at whether the potential provided by proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibition for prevention of atherosclerotic cardiovascular disease matches the excitement generated. Two fully human monoclonal antibodies to PCSK9 are currently licenced for clinical use both in the USA and the European Union: evolocumab and alirocumab. These reduce low-density lipoprotein cholesterol by over 50% across a range of populations and were generally found to have a safety profile comparable with placebo. The development programme for a third humanised monoclonal antibody, bococizumab, was terminated early due to the presence of neutralising antibodies reducing its efficacy over time. Results from the first cardiovascular outcomes trial, FOURIER, have demonstrated significant reductions in cardiovascular events in a population with stable cardiovascular disease over a 2-year period. The ODYSSEY OUTCOMES trial comparing alirocumab to placebo is expected to report in 2018 and provide cardiovascular outcome data in a post acute coronary syndrome population. Monoclonal antibodies have an injection burden of 12–26 injections per year. An alternative approach to reducing PCSK9 is to inhibit translation of the messenger RNA for PCSK9. The phase II ORION-1 study using inclisiran, a small interference RNA to PCSK9, suggested that two doses of inclisiran produced time averaged reductions in LDL cholesterol of 50% over 9 months. The ORION-4 cardiovascular outcome trial will assess the cardiovascular benefits of two injections per year using inclisiran. With further outcome trials expected, appropriate patient selection will be key considering the higher drug costs of these therapies.